2002
DOI: 10.1007/s00418-002-0388-0
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes in experimental MDA-MB231 tumor angiogenesis

Abstract: The role of pericytes (PCs) during embryonic or tumor angiogenesis is a matter of debate. We studied the expression of cytoskeletal, membrane, and matrix markers in experimental tumors of the human mammary ductal adenoma MDA-MB231 cell line that were grown on avian chorioallantoic membranes (CAMs) from incubation day 10 to 18 (chick) or 8 to 15 (quail). The expression patterns of alpha-smooth muscle actin (alphaSMA) and desmin, of adhesion molecules beta1 integrin and neurothelin, and of fibronectin and lamini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Cross reactivity can occur with plasma cells, platelets and lymphocytes 10 . The monoclonal anti-a-smooth muscle actin is specific for the single isoform a-actin that is expressed by pericytes 5 and smooth muscle cells found in the vessel wall, although KURZ et al 8 found that aSMA was not a general marker for pericytes. The integrin anb3 is a heterodimeric cell membrane adhesion molecule that plays an important role in maturation of blood vessels of the stroma 7 and is purportedly expressed by angiogenic vessels 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Cross reactivity can occur with plasma cells, platelets and lymphocytes 10 . The monoclonal anti-a-smooth muscle actin is specific for the single isoform a-actin that is expressed by pericytes 5 and smooth muscle cells found in the vessel wall, although KURZ et al 8 found that aSMA was not a general marker for pericytes. The integrin anb3 is a heterodimeric cell membrane adhesion molecule that plays an important role in maturation of blood vessels of the stroma 7 and is purportedly expressed by angiogenic vessels 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among normal capillaries, α-SMA is expressed in precapillaries and postcapillaries, but not midcapillaries, whereas normal venular pericytes express α-SMA [34]. Kurz et al [35] reported that pericytes expressed desmin, but not α-SMA, at the early stages of capillary sprouting in avian chorioallantoic membrane tumor angiogenesis assays. On the other hand, Morikawa et al [36] reported that pericytes in large tumors uniformly expressed both α-SMA and desmin even on capillary-size vessels in three experimental mouse tumor models.…”
Section: Discussionmentioning
confidence: 99%
“…The avian chorioallantoic membrane (CAM) is an established system for studying vascular growth and remodeling (Patan et al 1993;Kurz et al 1995Kurz et al , 2003Schlatter et al 1997;Djonov et al 2000bDjonov et al , 2002, for evaluating growth factors or biocompatible materials (Wilting et al 1993(Wilting et al , 1996Kurz et al 1998;Ribatti et al 2001;Zwadlo-Klarwasser et al 2001;Hagedorn et al 2004;Parsons-Wingerter et al 2006;Hlushchuk et al 2007;Oates et al 2007), or angiogenesis-related processes like cell or tumor growth (Papoutsi et al 2000;Kurz et al 2002Kurz et al , 2004Hagedorn et al 2005;Lugassy et al 2007). When the role of vascular mural cells during embryonic angiogenesis received increasing attention about 10 years ago, we were among the Wrst to identify the cytoskeletal proteins desmin (DES) and -smooth muscle actin ( SMA) in cells of the CAM microvasculature and connective tissue; we showed that PDGF-B may stimulate myoWbroblast formation and formation of non-capillary microvessels (Oh et al 1998).…”
Section: Introductionmentioning
confidence: 99%